Annealed thin strip carbon steel surface strengthening method based on QPQ technology

Through the surface strengthening method based on QPQ technology, process parameters and base salt composition are optimized, and the problem of improving the comprehensive performance of annealed thin strip carbon steel with a thickness of less than 1.5mm is solved, and high-performance surface strengthening is achieved, avoiding the risk of contamination in traditional processes.

CN119843215APending Publication Date: 2025-04-18FUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510122196.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the comprehensive performance of annealed thin strip carbon steel with a thickness of less than 1.5mm, especially in terms of corrosion resistance, wear resistance and mechanical properties, and the traditional electrochromic plating process has environmental pollution and health risks.

Method used

Using a surface strengthening method based on QPQ technology, the controllable construction of the seepage structure is achieved by designing the base salt composition and optimizing key process parameters such as nitriding temperature and oxidation time, forming corrosion resistance and excellent strength and wear resistance comparable to duplex stainless steel.

Benefits of technology

The corrosion resistance, strength and wear resistance of annealed thin strip carbon steel is significantly improved, and environmental pollution and health risks of traditional electrochromic plating processes are avoided, and the waste liquid treatment cost is saved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843215A_ABST
    Figure CN119843215A_ABST
Patent Text Reader

Abstract

The invention discloses an annealed ribbon carbon steel surface strengthening method based on a QPQ technology, which comprises the following steps of: carrying out deoiling cleaning, drying, shot blasting and preheating treatment on annealed ribbon carbon steel, then carrying out salt bath nitridation, then carrying out air cooling, desalting cleaning, drying and shot blasting treatment after primary salt bath oxidation, and then carrying out secondary salt bath oxidation, and then air cooling, desalting cleaning and drying treatment are carried out again, and the surface-strengthened annealed thin strip carbon steel can be obtained. The strength of the annealed thin strip carbon steel treated through the method can be improved by 190%-300%, and the electrochemical corrosion performance can be improved by 1100%-5500%. The QPQ technology is applied to strengthening the annealed thin strip carbon steel for the first time, novel QPQ treatment base salt and technological parameters which are highly matched with the QPQ technology are successfully developed, the corrosion resistance and excellent strength and abrasion resistance which are comparable with those of duplex stainless steel are achieved, and the QPQ technology can be used for replacing a traditional chromium electroplating technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal surface heat treatment, and in particular relates to a surface strengthening method for annealed thin strip carbon steel based on QPQ technology. Background Art

[0002] Annealed thin strip carbon steel is widely used in many fields such as umbrella manufacturing, petrochemical industry and automobile manufacturing due to its excellent plasticity, weldability and low cost. Especially in the umbrella manufacturing industry, the material needs to undergo complex curling deformation during the preparation process, which requires the material to be in an annealed state and thin (<1.5 mm), which poses a huge challenge to the corrosion resistance and wear resistance of the material. The existing modification method mainly uses electroplating chromium technology to improve its surface properties, but electroplating chromium has the following limitations: ① The process causes serious pollution to the environment and has potential hazards to human health; ② The effect of improving corrosion resistance and wear resistance is limited; ③ It cannot improve the comprehensive mechanical properties of the material, such as the negative impact of low strength on structural stability. Therefore, it is of great theoretical and engineering significance to develop a green and efficient surface strengthening technology to achieve the comprehensive performance optimization of thin strip carbon steel.

[0003] As a new type of liquid chemical heat treatment process, QPQ (Quench-Polish-Quench) salt bath composite treatment technology (hereinafter referred to as "QPQ technology") has attracted widespread attention for its excellent surface strengthening effect. QPQ technology is essentially a composite process of nitriding and oxidation treatment. Its core principle is to use the active nitrogen atoms generated by the decomposition of cyanate to diffuse into the material to form a nitriding layer on the surface of the substrate. The nitriding layer can significantly improve the strength, wear resistance and corrosion resistance of the material. For QPQ technology, when the nitriding temperature is lower than 590 ℃, it is called conventional QPQ technology, and the nitriding layer consists of a compound layer and a diffusion layer; when the nitriding temperature is higher than 590 ℃, it is called deep QPQ technology. At this time, an intermediate layer composed of nitrogen-containing austenite will be formed after the compound layer (transformed into nitrogen-containing martensite or nitrogen-containing troostite after air cooling or water cooling). In addition, oxidation treatment generates a dense Fe3O4 oxide layer through the internal diffusion of active oxygen atoms in the oxidizing salt bath, effectively filling the defects of the nitriding layer, and further improving the corrosion and wear resistance of the material.

[0004] There are few studies on QPQ technology in the field of thin strip carbon steel in the existing literature, especially for thin strip carbon steel workpieces with a thickness of less than 1.5 mm. Current research focuses on carbon steel samples with a larger thickness (5-15 mm), and its process design is usually based on single parameter optimization. However, for thinner materials, the composite structure of the nitriding layer and the oxidation layer must meet the following special requirements: ① Nitriding must effectively improve the strength and avoid embrittlement of the nitriding layer; ② The nitriding layer should be dense and uniform to prevent defects caused by excessive treatment and lead to performance degradation. These requirements make it difficult to fully solve the performance improvement needs by optimizing a single parameter. For example, too high nitriding temperature may cause the interface between the diffusion layer and the compound layer to become unstable, or a loose structure may appear on the surface of the compound layer, resulting in performance deterioration; and below a specific temperature range, the thickness of the nitriding layer is not enough to meet the actual application requirements. Therefore, the QPQ process of thin strip carbon steel needs to achieve the coordinated optimization of multiple parameters during the nitriding and oxidation treatments to balance the contradictions between wear resistance, corrosion resistance and mechanical properties.

[0005] At the same time, according to existing literature reports, the main ion composition of QPQ nitriding salts usually includes Na + , K + 、CNO - 、CO3 2- And trace amounts of CN - , while the main ions of oxidized salts include Na + , K + 、NO2 - 、CO3 2- and OH - The concentration and ratio of these ions have an important influence on the key physical and chemical properties of the salt bath, such as fluidity, stability, melting point and infiltration efficiency, and ultimately determine the differences in the infiltration layer structure and material strengthening properties. However, simple adjustments to the base salt composition often lead to complex interactions between multiple factors. For example, Li + Ions can significantly regulate CNO - The decomposition rate of Na + With K + The change of the ratio will affect the fluidity and stability of the salt bath, thereby affecting the diffusion rate; CNO - Too high or too low a concentration may lead to uneven structure of the carburized layer, or cause the carburized layer to be too thick or too thin, thus affecting the mechanical properties of the material. Therefore, the optimization of the base salt performance requires systematic composition analysis and design to achieve a balance in the comprehensive performance of the salt bath, thereby effectively meeting the synergistic optimization requirements of thin strip carbon steel in terms of strength, corrosion resistance and wear resistance. Therefore, the development and regulation of the base salt composition and the matching process are crucial to improving the strengthening effect. Summary of the invention

[0006] The purpose of the present invention is to provide a surface strengthening method for annealed thin strip carbon steel based on QPQ technology. The present invention applies QPQ technology to strengthen annealed thin strip carbon steel for the first time. By designing the base salt composition and optimizing key process parameters such as nitriding temperature and oxidation time, the controllable construction of the nitrided layer structure is achieved, so that the prepared annealed thin strip carbon steel can have corrosion resistance comparable to duplex stainless steel and excellent strength and wear resistance, while maintaining the elongation within the applicable range. At the same time, the method of the present invention solves the technical limitation that the traditional electrochromium plating process cannot achieve significant strength improvement. It not only avoids the environmental pollution and potential harm to human health caused by toxic hexavalent chromium ions in the hard chromium plating process, but also saves the waste liquid treatment cost to a great extent, providing technical support for the green manufacturing of high-performance thin strip steel.

[0007] To achieve the above object, the present invention adopts the following technical solution: A method for surface strengthening of annealed thin strip carbon steel based on QPQ technology, comprising the following steps: 1) Degreasing, cleaning, drying and shot blasting the annealed thin strip carbon steel; 2) Preheating the annealed thin strip carbon steel; 3) placing the preheated annealed thin strip carbon steel into molten nitriding salt for nitriding treatment; 4) placing the annealed thin strip carbon steel after nitriding treatment into molten oxidizing salt for primary oxidation treatment; 5) air cooling, desalting, cleaning, drying and shot blasting the annealed thin strip carbon steel; 6) placing the annealed thin strip carbon steel in an oxidizing salt for secondary oxidation treatment; 7) The annealed thin strip carbon steel is again subjected to air cooling, desalting cleaning and drying treatments.

[0008] Furthermore, the thickness of the annealed thin strip carbon steel is in the range of 0.5 to 1.5 mm.

[0009] Furthermore, the degreasing cleaning in step 1) is to immerse the annealed thin strip carbon steel in degreasing oil for 5 to 10 minutes, then ultrasonically clean it in warm water at 60 to 70°C for 15 to 30 minutes (ultrasonic frequency is 15 to 35 kHz), and finally rinse it with clean water for 10 to 20 minutes.

[0010] Furthermore, the preheating treatment in step 2) is to place the annealed thin strip carbon steel in a preheating furnace, maintain the temperature at 350-450 °C, and treat for 5-20 min. The preheating treatment has the following three main functions: first, to remove the residual moisture in the degreasing and cleaning process to avoid the presence of excessive moisture leading to a violent reaction in the nitriding process and causing safety accidents; second, to prevent the thin strip carbon steel from deforming. The large temperature difference between the cold thin strip carbon steel and the nitriding furnace may cause material deformation; third, to promote salt bath nitriding. After the preheating treatment, an Fe3O4 oxide layer will be generated on the surface of the annealed thin strip carbon steel, which is conducive to the penetration of nitrogen, thereby promoting the formation of nitrides.

[0011] Furthermore, the mass fraction of each ion in the molten nitride salt in step 3) is: Na + 20~40wt.%,K + 20~50 wt.%Li + 1~15 wt.%, CNO - 20~40 wt.%,CO3 2- 5~15 wt.%,MoO4 2- 1~10 wt.%,CN - :<0.15 wt.%,the sum of their mass fractions is 100 wt.%,and among them [Na + ] / [K + ]=0.5~1.5.

[0012] Furthermore, the temperature of the nitriding treatment in step 3) is 500-700°C and the time is 30-180 min. When the nitriding temperature is lower than 590°C, CNO - The mass fraction of CNO should be in the range of 30~40 wt.%; when the nitriding temperature is higher than 590 °C, - The mass fraction range should be 20~30 wt.%.

[0013] Furthermore, the mass fraction of each ion in the molten oxide salt in step 4) is: Na + 30~60wt.%,K + 10~30 wt.%, NO3 2- 10~30 wt.%, NO2 - 5~15 wt.%,CO3 2- 5~20 wt.%,OH - 5~25 wt.%,B4O7 2- 1~10 wt.%, the sum of their mass fractions is 100 wt.%.

[0014] Furthermore, the temperature of the primary oxidation treatment in step 4) is 400-500°C and the time is 10-30 min.

[0015] Furthermore, the temperature of the secondary oxidation treatment in step 6) is 400-500°C, and the time is 30-90 min.

[0016] Furthermore, during the operation, the drying is to place the annealed thin strip carbon steel in a drying chamber, maintain the temperature at 80±5°C, and process for 10-15 min.

[0017] Furthermore, during operation, the shot blasting is performed using a single-hook shot blasting cleaning machine, with a frequency set to 45-60 Hz and a time of 10-20 min.

[0018] Furthermore, in operation, after oxidation treatment, the air cooling time of the annealed thin strip carbon steel is 20 to 40 min.

[0019] Furthermore, during operation, the desalting cleaning is performed by rinsing with cold water for 10 to 20 minutes, and the water in the water tank is agitated by compressed air during the rinsing.

[0020] In view of the characteristics of annealed thin strip carbon steel, the present invention has developed a highly matched new QPQ treatment base salt and matching process parameters for the first time. The system is designed and the composition ratio of nitriding salt and oxidizing salt, nitriding temperature and time are regulated to achieve the synergistic effect of nitriding and oxidation processes. In addition, it is found during the research process that when the parameters deviate from the specified range (such as salt bath CNO ⁻ concentration is lower than 20%), the performance of the carburized layer will be greatly reduced and cannot meet the actual needs. This result shows that the dynamic design and regulation of multiple parameters are the key to ensuring the effectiveness of process matching. Ultimately, while keeping the material elongation within the applicable range, this process achieves the corrosion resistance of carbon steel comparable to that of duplex stainless steel and excellent strength and wear resistance, significantly broadening the application of QPQ technology in the field of thin-strip carbon steel materials, so that the prepared annealed thin-strip carbon steel can be widely used in industries such as umbrella manufacturing that have special requirements for thin steel performance.

[0021] The present invention has the following significant advantages: (1) The present invention applies QPQ technology to strengthen annealed thin strip carbon steel for the first time, and realizes the controllable construction of the nitrided layer structure by developing and designing the base salt composition and optimizing key process parameters such as nitriding temperature and oxidation time. The research results show that compared with conventional and deep QPQ technologies, the new QPQ treatment base salt can show excellent stability, and the process parameters that are highly matched with it have been successfully developed, achieving the corrosion resistance of annealed thin strip carbon steel comparable to that of duplex stainless steel, as well as excellent strength and wear resistance, while maintaining the elongation within the applicable range. It is worth mentioning that even without the use of sealing treatment, the corrosion resistance of the thin strip carbon steel prepared by this method can be improved by an astonishing 54 times, showing excellent technical advantages and application prospects. In addition, except for the differences in workpiece thickness, base salt composition and nitriding process parameters, the remaining operations in the method of the present invention are highly similar, which can greatly improve the efficiency of industrial production.

[0022] (2) The present invention significantly improves the mechanical properties of the material, especially in terms of strength. Therefore, the method of the present invention makes up for the technical limitation that the traditional electrochromium plating process cannot achieve significant strength improvement. In addition, compared with the toxic hexavalent chromium ion pollution often associated with the electrochromium plating process, the present invention provides a more environmentally friendly and harmless surface modification technology to human health, which is not only more in line with the status quo of green manufacturing and sustainable development, but also saves the cost of waste liquid treatment to a great extent.

[0023] (3) The enhanced carburized layer prepared by the method of the present invention achieves a more stable metallurgical bond with the substrate. Compared with traditional coatings, the surface enhanced layer obtained by this method not only provides significant protection performance, but also avoids the accelerated corrosion caused by the adverse reaction between the degradation products and the metal substrate, thereby effectively extending the service life of the material and reducing the risk of failure. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The scanning secondary electron micrographs of the cross sections of the initially annealed Q195 carbon steel strip and the annealed Q195 carbon steel strip after treatment in Examples 1 to 4 are shown.

[0025] Figure 2 The engineering stress-strain curves of the initial annealed Q195 carbon steel strip and the annealed Q195 carbon steel strip after treatment in Examples 1 to 4 are shown.

[0026] Figure 3 Graphs showing the polarization curves of the initially annealed Q195 carbon steel strip and the annealed Q195 carbon steel strip after treatment in Examples 1 to 4. DETAILED DESCRIPTION

[0027] A method for surface strengthening of annealed thin strip carbon steel based on QPQ technology, comprising the following steps: 1) Soak the annealed thin strip carbon steel with a thickness of 0.5-1.5 mm in decontamination oil for 5-10 minutes, then ultrasonically clean it in warm water at 60-70 °C for 15-30 minutes (ultrasonic frequency is 15-35 kHz), then rinse it with clean water for 10-20 minutes, and then dry it and shot blast it; 2) Place the annealed thin strip carbon steel in a preheating furnace, maintain 350~450℃, and preheat for 5~20 minutes; 3) Place molten nitriding salt in the nitriding furnace, then place the preheated annealed thin strip carbon steel into the nitriding furnace for nitriding treatment at 500~700℃ for 30~180min; 4) Place molten oxide salt in the oxidation furnace, then place the annealed thin strip carbon steel after nitriding into the oxidation furnace, and perform a primary oxidation treatment at 400~500℃ for 10~30 min; 5) Air cool the annealed thin strip carbon steel for 20-40 min, then desalt, clean, dry and shot blast; 6) Place the annealed thin strip carbon steel into the oxidation furnace again and perform secondary oxidation treatment at 400-500 °C for 30-90 min; 7) The annealed thin strip carbon steel is air-cooled again for 20 to 40 minutes, and then desalted, cleaned and dried.

[0028] Wherein, the mass fraction of each ion in the molten nitride salt in step 3) is: Na + 20~40wt.%,K + 20~50 wt.%Li + 1~15 wt.%, CNO - 20~40 wt.%,CO3 2- 5~15 wt.%,MoO4 2- 1~10 wt.%,CN - :<0.15 wt.%,the sum of their mass fractions is 100 wt.%,and [Na + ] / [K + ]=0.5~1.5.

[0029] The mass fraction of each ion in the molten oxide salt in step 4) is: Na + 30~60 wt.%, K + 10~30 wt.%, NO3 2- 10~30 wt.%, NO2 - 5~15 wt.%,CO3 2- 5~20 wt.%,OH - 5~25 wt.%,B4O72- 1~10wt.%, and the sum of their mass fractions is 100 wt.%.

[0030] During the operation, the drying is to place the annealed thin strip carbon steel in a drying chamber, maintain the temperature at 80±5°C, and treat for 10-15 minutes. The shot blasting is performed using a single hook shot blasting cleaning machine, the frequency of which is set to 45-60 Hz, and the time is 10-20 minutes. The desalting cleaning is performed by cold water rinsing for 10-20 minutes, during which the water in the water tank is stirred by compressed air.

[0031] The present invention will be described in detail below in conjunction with the accompanying drawings.

[0032] The present invention and its implementation methods are described below, which are not restrictive and the actual implementation methods are not limited thereto. In short, if ordinary technicians in the field are inspired by it and design structural methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

[0033] Example 1 A surface strengthening method for annealed thin strip carbon steel based on QPQ technology is applied to annealed Q195 thin strip carbon steel, which is specifically carried out according to the following process: In the first step, the annealed Q195 thin strip carbon steel with a thickness of 1.2 mm is immersed in decontamination oil for 5 minutes to completely remove the oil on the surface (if the surface oil is extremely serious, the immersion time can be appropriately increased); then the annealed Q195 thin strip carbon steel is placed in an ultrasonic cleaning machine, the ultrasonic frequency is set to 25 kHz, and ultrasonic cleaning is performed using 65 ℃ warm water for 30 minutes, and finally rinsed with clean water for 15 minutes; then the cleaned annealed Q195 thin strip carbon steel is placed in a drying room, maintained at a temperature of 80±5℃, and dried for 10 minutes to ensure that the surface is dry; then the dried annealed Q195 thin strip carbon steel is placed in a single hook shot blasting cleaning machine for shot blasting, the frequency of which is set to 50 Hz, and the time is 10 minutes; In the second step, the annealed Q195 thin strip carbon steel is placed in a preheating furnace at a furnace temperature of 350 °C for 5 min. In the third step, the preheated annealed Q195 thin strip carbon steel is placed in a nitriding furnace filled with molten nitriding salt, the furnace temperature is maintained at 580 °C, and the nitriding is performed for 90 min; the mass fractions of the ions in the molten nitriding salt are as follows: Na + 24wt.%K + 24 wt.%([Na + ] / [K + ]=1.0), Li +5 wt.%, CNO - 35 wt.%,CO3 2- 7 wt.%,MoO4 2- 4.95 wt.%, CN - 0.05 wt.%; In the fourth step, the annealed Q195 thin strip carbon steel processed in the above step is placed in an oxidation furnace filled with molten oxidizing salt, the furnace temperature is maintained at 450 ° C, and the oxidation is carried out for 15 min; the mass fraction of each ion in the molten oxidizing salt is as follows: Na + 35 wt.%, K + 15 wt.%, NO3 2- 12 wt.%, NO2 - 6 wt.%,CO3 2- 7 wt.%,OH - 20 wt.%, B4O7 2- 5 wt.%; The fifth step is to air cool the oxidized annealed Q195 carbon steel strip for 30 minutes; then rinse it with cold water for 15 minutes (the water in the water tank is stirred by compressed air during the rinsing period), and then place the annealed Q195 carbon steel strip in a drying room, maintain the temperature at 80 °C, and dry it for 10 minutes; In the sixth step, a single-hook shot blasting machine is used to shot blast the dried annealed Q195 thin strip carbon steel. The frequency is set to 50 Hz and the time is 10 min to remove the defects such as looseness, shrinkage and roughness that may exist on the surface of the annealed Q195 thin strip carbon steel. Step 7: Place the annealed Q195 thin strip carbon steel in an oxidation furnace, keep the furnace temperature at 450 °C, and perform secondary oxidation for 60 minutes to replenish the damaged oxide film layer; Step 8. After completing the above steps, the annealed Q195 thin strip carbon steel is air-cooled for 30 minutes, then rinsed with cold water for 15 minutes, and finally placed in a drying room, maintained at 80°C, and dried for 10 minutes.

[0034] Example 2 This embodiment is based on Embodiment 1, and the difference between this embodiment and Embodiment 1 is that: In the third step, the temperature of the nitriding furnace is maintained at 620 °C and the nitriding is performed for 120 min. The mass fractions of the ions in the molten nitriding salt are as follows: Na + 22 wt.%, K + 33 wt.%([Na + ] / [K + ]=0.67), Li + 8 wt.%, CNO - 25 wt.%,CO32- 5wt.%MoO4 2- 6.95 wt.%, CN - : 0.05 wt.%.

[0035] Example 3 This embodiment is based on Embodiment 1, and the difference between this embodiment and Embodiment 1 is that: 1) The thickness of annealed Q195 carbon steel strip is 0.8 mm; 2) In the third step, the temperature of the nitriding furnace is maintained at 540 °C for 120 min.

[0036] Example 4 This embodiment is based on Embodiment 2, and the difference between this embodiment and Embodiment 2 is that: 1) The thickness of annealed Q195 carbon steel strip is 0.8 mm; 2) In the third step, the temperature of the nitriding furnace is maintained at 620 °C for nitriding for 60 min.

[0037] Comparative Example 1 This comparative example is based on Example 1, and the difference between it and Example 1 is: In the third step, the temperature of the nitriding furnace was maintained at 620 °C and the nitriding was performed for 120 min.

[0038] Comparative Example 2 This comparative example is based on Example 1, and the difference between it and Example 1 is: In the third step, the mass fraction of each ion in the molten nitride salt is as follows: Na + 35 wt.%, K + 20 wt.%([Na + ] / [K + ]=1.75), Li + 5 wt.%, CNO - 35 wt.%,CO3 2- 7 wt.%,MoO4 2- 4.95 wt.%, CN - 0.05 wt.%.

[0039] Comparative Example 3 This comparative example is based on Example 1, and the difference between it and Example 1 is: In the third step, the temperature of the nitriding furnace is maintained at 580 °C and the nitriding time is 200 min.

[0040] Comparative Example 4 This comparative example is based on Example 1, and the difference between it and Example 1 is: The seventh step of secondary oxidation treatment is omitted.

[0041] 1. The scanning secondary electron microscopy of the cross section of the annealed Q195 thin strip carbon steel after treatment in Examples 1 to 4 is shown in Figure 1 . Figure 1 The results show that the annealed Q195 thin strip carbon steel of different thicknesses treated in Example 1 and Example 3 (both belong to the category of conventional QPQ technology) has a diffusion layer mainly composed of an oxide film layer, a compound layer and a diffusion layer. In Example 2 and Example 4 (both belong to the category of deep QPQ technology), an intermediate layer composed of nitrogen-containing austenite is formed after the annealed Q195 thin strip carbon steel of different thicknesses is treated, and the appearance of the intermediate layer is attributed to the phase transformation of the Fe-N phase when the nitriding temperature is higher than 590 ° C. The intermediate layer will be transformed into nitrogen-containing troostite during air cooling. At the same time, the figure also shows that the annealed Q195 thin strip carbon steel treated in Example 2 and Example 4 has a significantly higher diffusion layer thickness than that in Example 1 and Example 3. This is because the higher nitriding temperature significantly increases the diffusion rate of active nitrogen atoms. In addition, the diffusion layer shown in the figure has the characteristics of uniformity and density, which can provide the material with better comprehensive performance.

[0042] 2. The annealed Q195 thin strip carbon steel after treatment in the embodiment and the comparative example was subjected to tensile test along the rolling direction, and the obtained engineering stress-strain curve is shown in Figure 2 , and compared with the initial annealed Q195 thin strip carbon steel, the specific results are shown in Table 1.

[0043] Table 1 Comparison of mechanical properties of carbon steels in various embodiments of the present invention and those reported in other literatures

[0044] As can be seen from Table 1, the yield strength of the annealed Q195 thin strip carbon steel after treatment in Example 1 increased from 193.1 MPa of the initial annealed Q195 thin strip carbon steel (thickness 1.2 mm) to 374.4 MPa, the tensile strength increased from 258.0 MPa to 501.2 MPa, and the elongation decreased from 45.0% to 24.2%; the yield strength of Example 2 increased to 481.8 MPa, the tensile strength increased to 595.6 MPa, and the elongation decreased to 17.3%; the yield strength of Example 3 increased from 151.5 MPa of the initial annealed Q195 thin strip carbon steel (thickness 0.8 mm) to 422.8 MPa, the tensile strength increased from 220.0 MPa to 606.8 MPa, and the elongation decreased from 43.2% to 23.0%; the yield strength of Example 4 increased to 408.3 MPa, the tensile strength increased to 541.2 MPa, and the elongation is reduced to 21.0%. It can be seen that the yield strength and tensile strength of the annealed Q195 thin strip carbon steel treated by the method of the present invention are significantly improved, while the reduction in elongation is within the usable range, and its effect is better than that of the comparative example.

[0045] 3. The corrosion resistance test was conducted by electrochemical method using CHI 660E electrochemical workstation. The electrochemical experiment used a three-electrode system, with a 3.5% NaCl aqueous solution as the test medium, a Pt electrode as the counter electrode, a saturated calomel electrode as the reference electrode, and an annealed Q195 thin strip carbon steel sample as the working electrode. The area immersed in the test medium was 1 cm 2 Before the polarization test, a 4000 s open circuit potential test is required to ensure that it reaches a relatively stable state (open circuit potential fluctuation value within 100 seconds: within 1 mV). During the polarization test, the scanning potential range is set to -0.5 V~+1.5 V (relative to the open circuit potential), and the scanning rate is 0.5 mV / s. The obtained polarization curve is shown in Figure 3 The specific results are shown in Table 2.

[0046] Table 2 Comparison of electrochemical corrosion performance of carbon steel in various embodiments of the present invention and other literature reports

[0047] The results in Table 2 show that the self-corrosion current density of the annealed Q195 carbon steel strip (thickness 1.2 mm) after treatment in Example 1 increased from 9.20 μA·cm -2 Reduced to 0.60 μA·cm -2 ; The self-corrosion current density of Example 2 was reduced to 0.45 μA·cm -2 The self-corrosion current density of the annealed Q195 carbon steel strip (thickness 0.8 mm) after treatment in Example 3 increased from 15.70 μA·cm -2 Reduced to 1.35 μA·cm -2 The self-corrosion current density of Example 4 was reduced to 0.29 μA·cm -2 , and its effect is better than that of the comparative example.

[0048] In summary, the method of the present invention applies QPQ technology to strengthen annealed thin strip carbon steel for the first time, and successfully develops a new QPQ treatment base salt and process parameters that are highly matched with it. By analyzing the data in Tables 1 and 2, it can be seen that after being treated by this method, the strength and corrosion resistance of the annealed thin strip carbon steel are significantly improved, achieving corrosion resistance comparable to that of duplex stainless steel and excellent strength and wear resistance. On the basis of the scheme of the present invention, if the process parameters (Comparative Examples 1 and 3), the formula of the nitriding salt (Comparative Example 2) or the adjustment of the operating steps (Comparative Example 4) are changed, the comprehensive performance will be significantly deteriorated, which further reflects the limiting significance of the technical scheme of the present invention. At the same time, compared with other documents, the carbon steel treated by the method of the present invention can show significant advantages in strength improvement (such as the tensile strength of Comparative Example 5 is increased by about 134% compared with its initial material, while the carbon steel treated by the method of the present invention can be increased by 190%~300% compared with the initial material; and the quenching and partitioning process used in Comparative Example 5 has high requirements for operating accuracy, and fails to achieve a synchronous improvement in corrosion resistance). Further comparison of Comparative Examples 6 and 7 shows that the method of the present invention is more effective in improving the corrosion resistance of thin strip carbon steel, thanks to the basic properties of the material, the regulation of base salts and related process parameters, avoiding the use of rare earth elements or composite treatment processes, thereby avoiding the use of high-cost raw materials. These characteristics fully demonstrate the significant advantages of the method of the present invention in terms of economy, practicality and comprehensive performance optimization.

[0049] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for surface strengthening of annealed thin strip carbon steel based on QPQ technology, characterized in that: The following steps are involved: 1) Degreasing, cleaning, drying and shot blasting the annealed thin strip carbon steel; 2) Preheating the annealed thin strip carbon steel; 3) placing the preheated annealed thin strip carbon steel into molten nitriding salt for nitriding treatment; 4) placing the annealed thin strip carbon steel after nitriding treatment into molten oxidizing salt for primary oxidation treatment; 5) air cooling, desalting, cleaning, drying and shot blasting the annealed thin strip carbon steel; 6) placing the annealed thin strip carbon steel in an oxidizing salt for secondary oxidation treatment; 7) The annealed thin strip carbon steel is again subjected to air cooling, desalting cleaning and drying treatments.

2. The method for surface strengthening of annealed thin strip carbon steel based on QPQ technology according to claim 1, characterized in that: The thickness of the annealed thin strip carbon steel is in the range of 0.5 to 1.5 mm.

3. The method for surface strengthening of annealed thin strip carbon steel based on QPQ technology according to claim 1, characterized in that: In step 1), the degreasing cleaning is to immerse the annealed thin strip carbon steel in degreasing oil for 5 to 10 minutes, then ultrasonically clean it in warm water at 60 to 70°C for 15 to 30 minutes, and finally rinse it with clean water for 10 to 20 minutes.

4. The method for surface strengthening of annealed thin strip carbon steel based on QPQ technology according to claim 1, characterized in that: The drying process is carried out at 80 ± 5 °C for 10 to 15 min.

5. The method for surface strengthening of annealed thin strip carbon steel based on QPQ technology according to claim 1, characterized in that: In step 2), the preheating treatment is carried out at 350-450°C for 5-20 min.

6. The method for surface strengthening of annealed thin strip carbon steel based on QPQ technology according to claim 1, characterized in that: In step 3), the mass fraction of each ion in the molten nitride salt is: Na + 20~40 wt.%, K + 20~50 wt.%Li + 1~15 wt.%, CNO - 20~40 wt.%,CO3 2- 5~15 wt.%,MoO4 2- 1~10 wt.%,CN - :<0.15 wt.%,the sum of their mass fractions is 100 wt.%,and among them [Na + ] / [K + ]=0.5~1.5; the temperature of the nitriding treatment is 500~700 °C, and the time is 30~180 min.

7. The method for surface strengthening of annealed thin strip carbon steel based on QPQ technology according to claim 1, characterized in that: In step 4), the mass fraction of each ion in the molten oxide salt is: Na + 30~60 wt.%, K + 10~30 wt.%, NO3 2- 10~30 wt.%, NO2 - 5~15 wt.%,CO3 2- 5~20 wt.%,OH - 5~25 wt.%,B4O7 2- 1~10wt.%, and the sum of their mass fractions is 100 wt.%.

8. The method for surface strengthening of annealed thin strip carbon steel based on QPQ technology according to claim 1, characterized in that: During the operation, the temperature of the primary oxidation treatment and the secondary oxidation treatment are both 400-500°C; the time of the primary oxidation treatment is 10-30 min, and the time of the secondary oxidation treatment is 30-90 min.

9. The method for surface strengthening of annealed thin strip carbon steel based on QPQ technology according to claim 1, characterized in that: During operation, the air cooling time of the annealed thin strip carbon steel after oxidation treatment is 20~40 min.

10. The method for surface strengthening of annealed thin strip carbon steel based on QPQ technology according to claim 1, characterized in that: During operation, the desalting cleaning is performed by rinsing with cold water for 10 to 20 minutes.